Meningkatkan Aktivitas Belajar Siswa Dengan Menggunakan Model Pembelajaran Kooperatif Tipe Make A Match Di Kelas V Sekolah Dasar - Fakhrezi, Berrly; Rizal, Muhammad Syahrul; Surya, Yenni Fitra (Science and Education Journal (SICEDU), 2022)
This research was motivated by the low learning activity of students on the theme 1 Animal and Human Movement Organs in class V SD Negeri 136 Pekanbaru. One solution to overcome this problem is to use the Make A Match type of cooperative learning model. The purpose of this study was to improve student learning activities on the theme 1 Animal and Human Movement Organs by using the Make A Match type of cooperative learning model. The subjects of this study were 30 grade V students, with 12 male students and 18 female students. The collection technique is in the form of documentation, observation, and tests. The results of this study can be concluded that the student's learning activities on the theme 1 Animal and Human Movement Organs in Cycle I Meeting 1 is 62.82% with a fairly active category. In Cycle I Meeting 2, student learning activities increased by 70.75% with a fairly active category. In Cycle II Meeting 1, student learning activities increased by 76.95% with the active category. In Cycle II Meeting 2, student learning activities increased by 81.54% with the active category. Thus, it can be concluded that using the Make A Match type of cooperative learning model can improve student learning activities.